Preoperative edema severity affects outcomes after Descemet membrane endothelial keratoplasty for Fuchs endothelial corneal dystrophy: a cohort study - Friedrich, Maximilian; Son, Hyeck Soo; Lind, Jasper; Hammer, Maximilian; Chychko, Lizaveta; Yildirim, Timur Mert; Auffarth, Gerd U.; Augustin, Victor A. (Eye and Vision, 2025)
In patients with Fuchs endothelial corneal dystrophy (FECD), the most beneficial stage to perform Descemet membrane endothelial keratoplasty (DMEK) remains uncertain. The goal of this study was to compare the surgical outcomes after DMEK in FECD patients with subclinical corneal edema and clinical corneal edema to test the hypothesis of whether performing surgery in subclinical corneal edema stages achieves better surgical outcomes.